2012
DOI: 10.1590/s0101-20612012005000112
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane spirit market share simulation: an application of conjoint analysis

Abstract: This study evaluated the influence of packaging and labeling attributes of sugarcane spirit on consumers' behavior by applying the results of conjoint analysis in sugarcane spirit market share simulation. Firstly, a conjoint analysis was performed aiming to estimate the part-worths of each consumer for some sugarcane spirit packaging and labeling attributes. These part-worths were used in the market share simulation using the maximum utility model. It was observed that some packaging and labeling attributes af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Similar to the present study, the research by Carneiro et al (2012) about the factors of the packaging and label of cachaça in the consumers behavior verified that the additional information positively influenced the consumers of Viçosa-MG, enriching the contents of the packaging. Oenning et al (2017) found similar results about the presence of additional information and an innovative shape on the processed tomato packaging.…”
Section: Resultssupporting
confidence: 88%
“…Similar to the present study, the research by Carneiro et al (2012) about the factors of the packaging and label of cachaça in the consumers behavior verified that the additional information positively influenced the consumers of Viçosa-MG, enriching the contents of the packaging. Oenning et al (2017) found similar results about the presence of additional information and an innovative shape on the processed tomato packaging.…”
Section: Resultssupporting
confidence: 88%
“…Recently, in a study where they predicted the market share of products through conjoint analysis, Guyon and Petiot () developed a new logit technique that can be used in rank‐based conjoint analysis to increase its predictive validity. In addition, Carneiro et al () conducted a study in which they used conjoint analysis to investigate the features and feature levels of a sugarcane spirit and predict its market share. Baglyas () applied conjoint analysis and estimated the part‐worth of product features of wine, such as region, taste, quality, manufacturing methods and price, and used this information to investigate the relationship between consumer characteristics and product features, which could be useful in the development of new wines.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the illustration was also observed in other studies. Carneiro et al. (2012) also found it as a relevant factor in the purchase decision process of sugar cane rum.…”
Section: Resultsmentioning
confidence: 91%
“…The importance of the illustration was also observed in other studies. Carneiro et al (2012) also found it as a relevant factor in the purchase decision process of sugar cane rum. Caleguer et al (2007) observed that the presence of the fruit and a glass with the beverage in it on the label was considered to be important in the assessment of labels of orange refreshment powder.…”
Section: Purchase Intension Regarding the Labels Developedmentioning
confidence: 91%